2021
DOI: 10.1177/15248399211024996
|View full text |Cite
|
Sign up to set email alerts
|

Emphasizing Choice and Autonomy in Personal Hygiene, Menstrual Health, and Sexual Health Product Distribution to People Experiencing Homelessness in Atlanta, Georgia During COVID-19

Abstract: The Dignity Pack Project is a small-scale, crisis-oriented supply chain in Atlanta, Georgia, designed to meet the acute personal hygiene,menstrual health, and sexual health needs of people experiencing homelessness (PEH). It was organized in response to conditions during the COVID-19 pandemic that continue to illuminate and exacerbate the distinct and complex challenges PEH face when trying to meet their basic needs and maintain their health. In addition to being particularly vulnerable to COVID-19 due to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…However, more research is needed as to the specific barriers, whether that be policies, stigma, or availability of medication, to pain management within homeless service providers. This issues of supplies corroborated in investigations in other cities [ 20 , 21 , 57 , 58 ], indicating the menstruation experience of PEH as a whole is complicated by inadequate access to necessary items and services.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, more research is needed as to the specific barriers, whether that be policies, stigma, or availability of medication, to pain management within homeless service providers. This issues of supplies corroborated in investigations in other cities [ 20 , 21 , 57 , 58 ], indicating the menstruation experience of PEH as a whole is complicated by inadequate access to necessary items and services.…”
Section: Discussionsupporting
confidence: 62%
“…Our study advances reproductive and public health research goals by illuminating PEH’s challenges when managing menstruation in Indiana. It contributes to the national dialogue on the importance of addressing these barriers, through increasing product and hygienic space access [ 21 , 48 , 58 ], changing policies [ 34 , 61 ], and improving period equity [ 62 ]. Additionally, our study draws attention to critical gaps at organizational and policy levels in menstruation-related services to better integrate menstruation into health and well-being programs for PEH.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research has suggested that access to private showers, restrooms, and running water within day centres for PEH promote a greater sense of security and safety [ 168 , 169 ]. Therefore, increasing availability and access to private restrooms and hygienic resources could have twofold benefits: increased engagement with personal hygiene and compliance with COVID-19 guidelines [ 11 , 40 , 88 , 170 , 171 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Other studies have focused on understanding the menstrual self-care practices and menstrual health challenges of women and girls in humanitarian contexts, as well as the acceptability of specific menstrual products in such settings. [9][10][11] More recently, studies have started to describe challenges for adult women, [12][13][14][15] marginalized populations in high income countries (HICs), [16][17][18][19][20] , mental health, 21 and to develop measures for menstrual health research. 22,23 The evidence on menstrual health has been consolidated in a growing body of systematic reviews, including reviews focused on specific geographies, [24][25][26] populations (e.g.…”
Section: Introductionmentioning
confidence: 99%